SPATIAL ANALYSIS OF LANDSLIDES USING GIS. CASE STUDY: TÂRNAVELOR PLATEAU - ROȘIAN, Gheorghe; HORVATH, Csaba; MUNTEAN, Liviu; BACIU, Nicolae; MӐCICӐŞAN, Vlad; MALOȘ, Cristian (Studia Universitatis Babeș-Bolyai Ambientum, 2019)
Landslides represent one of the most important hazardous geomorphological phenomena in the Târnavelor Plateau. Geographically this unit is positioned on the southern part of the Transylvanian Depression. For the landslides distribution analysis, we used five criteria: geology, slope, altitude, exposition and the local administrative units. This type of studies is a must, on one hand to find out how the current landslides are distributed, and on the other hand to identify the areas which are prone to this type of hazardous geomorphological phenomena. By investigating the study area’s ortophotoplans and topographic maps, 5797 landslides were vectorized to create a landslide inventory map. The study shows that lithologic conditions (the presence of friable rocks such as marls, clays, sand) and the land use (mostly agricultural lands) are the most defining factors for landslide to develop, it is believed that in the future landslides will appear on similar slope, orientation and geological conditions etc. In this situation, knowing the susceptible areas to landslides is beneficial for the territorial planning actions and also to avoid the building and expanding other civil engineering constructions on lands which are prone to landslides.